Adaptação transcultural e validação do questionário de comportamento de sono do atleta - Lucas Alves Facundo (2020)
Sleep plays a fundamental role for physical and cognitive recovery and, consequently, for the sports performance. Therefore, several tools such as actigraphy and polysomnography are used to monitor sleep. However, these last tools offer high cost, leading to the development of questionnaires to analyze the sleep-wake cycle. Among the questionnaires, we can mention the Pittsburg Sleep Quality Index and Epworth Sleepiness Scale, valid for use in Brazil, but not for athletes. In view of the particularities of the sports context and its influence on sleep, the “Athlete's Sleep Behavior Questionnaire” (ASBQ) was developed, but it has not validated for the Portuguese language yet. The aim of the present study was to perform a cross-cultural adaptation and analyze reliability test-retest and discriminant validity for the Brazilian population. To fulfill this objective, a cross-cultural adaptation of the questionnaire went through translation and reverse translation procedures. We also performed content validation by nine experts, calculating the Coefficient of Content Validity (CVC) for the equivalence of the items and the total scale for the construct “sleep behavior”, in addition we made a pilot study. To answer the ASBQ, we recruited 104 participants, allocated in two groups: 52 athletes and 52 non-athletes. The reliability test of the questionnaire was carried out in an interval of seven days and was accessed through the intraclass correlation coefficient (ICC) and by the Cronbach’s α. In addition, we performed the discriminant validity by comparing the scores between the groups. As a result, ASBQ went through the process of cross-cultural adaptation, generating a Brazilian version of ASBQ (ASBQ-BR) and presenting acceptable values in the CVC. Additionally, the ASBQ-BR presents acceptable values of reliability (ICC = O,857; Cronbach’s α=0,78) and difference between athletes and non-athletes scores, sport related factors and items (p<0,05). In conclusion, we performed the translation from ASBQ to ASBQ-BR and guaranteed its sensitivity and reliability. ASBQ-BR is an important tool in monitoring athletes' sleep hygiene.